2012
DOI: 10.1097/jgp.0b013e31822cccff
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Older Patients With the Atypical Features of Interpersonal Rejection Sensitivity and Reversed-Vegetative Symptoms are Similar to Younger Atypical Patients

Abstract: Objectives The atypical depression (AD) subtype has rarely been examined in older patients. However, younger AD patients have been characterized as having more severe and chronic symptoms of depression compared with non-AD patients. Design Secondary data analysis using ANOVAs and Growth Curve Modeling. Setting Clinical Research Center for the Study of Depression in Later Life. Participants Depressed older patients (N=248) followed over 2 years. Method In a longitudinal study, we examined depression sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Participants were then asked to identify the depressive symptoms present during that worst episode. The symptom list included items that would be characterized as "melancholic" (e.g., loss of appetite, weight loss, and excessive guilt) and those that would be characterized as "atypical" (e.g., increased appetite, weight gain, and increased sleep) (Sachs-Ericsson et al, 2012).…”
Section: Worst Episodementioning
confidence: 99%
“…Participants were then asked to identify the depressive symptoms present during that worst episode. The symptom list included items that would be characterized as "melancholic" (e.g., loss of appetite, weight loss, and excessive guilt) and those that would be characterized as "atypical" (e.g., increased appetite, weight gain, and increased sleep) (Sachs-Ericsson et al, 2012).…”
Section: Worst Episodementioning
confidence: 99%
“…chronic course, duration index episode, number of episodes). [17][18][19][20][21][22] Only a few prospective studies have evaluated differences in course of depressive subtypes, with one study finding no difference in course between atypical and non-atypical depression, 23 another study finding an initial slower symptom severity recovery but similar severity end-points 24 and one study finding no difference in clinical outcome. 25 One study found the atypical subtype to be a predictor of obesity.…”
mentioning
confidence: 99%
“…In some cases, they also refuse to eat, drink or use medication, and they may start having problems with self-care. [10][11]…”
Section: Depression and Anxiety During The Covid-19 Pandemicmentioning
confidence: 99%